Blessings in Trade According to The Views of Banjar Traders in Palangka Raya City with An Anthropological and Religious Approaches - Kurniawan, Rahmad; Rofiq , Aunur; Khusnudin (Universitas Al-Qolam Malang, 2024)
Islam requires every mature individual to seek legal livelihood, one of which is through trade. However, some traders sometimes do not pay attention to the provisions of Islamic commercial transactions (muamalah). In this regard, there is an interesting phenomenon among some Banjar traders at the Pasar Besar in Palangka Raya. They emphasize more on the concept of